Analysis of stroke, coordinative and temporal parameters in transition from underwater to surface swimming - Navandar, A.; Veiga, S.; Garcia, I.; Navarro, E. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The objective of this study was to characterize the stroking, coordinative and temporal parameters of international swimmers during transition from underwater to surface swimming. 12 international junior swimmers were filmed on the four strokes and they wre video analysed using DLT-20 algorithms to calculate the swimming velocity, stroking rate and stroking length at emersion as well as the index of coordination (IdC) and the % of each stroke phase duration on the complete cycle. The descriptive analysis of these data showed higher swimming velocity, stroking rate and IdC but shorter stroking length than previous studies characterizing free swimming. Also, the relative duration of the non-propulsive stroke phases was shorter when emerging from underwater. Therefore, the stroke, coordinative and temporal parameters should also be monitored during the transition phase of the swimming start and turns.